2024
DOI: 10.1177/03635465231220855
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic Acid Attenuates the Progression of Posttraumatic Osteoarthritis in Mice

Weixin Xie,
Shan Jiang,
Antonia Donat
et al.

Abstract: Background: Posttraumatic osteoarthritis (OA) is a common disorder associated with a high socioeconomic burden, particularly in young, physically active, and working patients. Tranexamic acid (TXA) is commonly used in orthopaedic trauma surgery as an antifibrinolytic agent to control excessive bleeding. Previous studies have reported that TXA modulates inflammation and bone cell function, both of which are dysregulated during posttraumatic OA disease progression. Purpose: To evaluate the therapeutic effects of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…A recent animal study with a sample size of 6 showed that both systemic and topical TXA treatment protected cartilage from degeneration and lowered inflammatory responses of the synovial tissue in mice with post-traumatic osteoarthritis after anterior cruciate ligament transection. Moreover, systemic TXA beneficially affected pathological subchondral bone remodeling and reduced osteophyte formation in wild-type mice that underwent anterior cruciate ligament transection 22 , overall suggesting a potentially beneficial effect of TXA in patients with osteoarthritis. Thus, the results of a current phase II double-blinded RCT investigating the effects of systemic TXA on joint inflammation and cartilage health in anterior cruciate ligament reconstruction are eagerly awaited 77 .…”
Section: Preclinical Evaluations Of Txa In Skeletal Diseasesmentioning
confidence: 94%
See 2 more Smart Citations
“…A recent animal study with a sample size of 6 showed that both systemic and topical TXA treatment protected cartilage from degeneration and lowered inflammatory responses of the synovial tissue in mice with post-traumatic osteoarthritis after anterior cruciate ligament transection. Moreover, systemic TXA beneficially affected pathological subchondral bone remodeling and reduced osteophyte formation in wild-type mice that underwent anterior cruciate ligament transection 22 , overall suggesting a potentially beneficial effect of TXA in patients with osteoarthritis. Thus, the results of a current phase II double-blinded RCT investigating the effects of systemic TXA on joint inflammation and cartilage health in anterior cruciate ligament reconstruction are eagerly awaited 77 .…”
Section: Preclinical Evaluations Of Txa In Skeletal Diseasesmentioning
confidence: 94%
“…Collectively, the current evidence from animal experiments suggests beneficial effects of TXA on osteoporosis 21 and osteoarthritis 22 , while the underlying mechanisms however, require further clarification. In terms of bone regeneration, the results from one preclinical study support a positive effect of TXA application on fracture healing 70 , whereas the other two available studies suggest no influence 72 or even negative outcomes 71 .…”
Section: Preclinical Evaluations Of Txa In Skeletal Diseasesmentioning
confidence: 98%
See 1 more Smart Citation